Effective Teaching Around the World Theoretical, Empirical, Methodological and Practical Insights - Maulana, Ridwan; Helms-Lorenz, Michelle; Klassen, Robert M. (Springer Nature, 2023)
This open access book brings together theoretical, empirical, methodological, and practical insights from various countries on effective teaching. It particularly focuses on discussing issues pertaining to effective teaching behaviour including definitions and conceptualizations, measurement, differences, and importance to student outcomes from international perspectives. The book will draw upon the rich cultures with diverse contexts involving Asia, Australia, Africa, America, and Europe which serve as the background setting to better understand teaching quality from a wide spectrum of educational systems and performances. It shows that effective teaching behaviour can be conceptualized and operationalized uniformly using specific frameworks and measures, but also addresses some limitations that should be tackled. The book discusses promising ways to measure and compare effective teaching behaviour from classical test theory (CTT) as well as item response theory (IRT) perspectives. It indicates that effective teaching behaviour in diverse countries follows a systematic level of complexity, which provides an avenue for ongoing teacher education and teacher professional development. It discusses the interrelated domains of effective teaching behaviour including contemporary trends of differentiation. The book continues with examining similarities and differences in effective teaching behaviour across countries. It builds on the understanding of cultural traditions across countries as profoundly reflected in the classroom processes.